Incorporating Peer Mentor Tutorials Into a Success Course for Diverse Students - Sheilagh Grills (JANZSSA)
This paper describes weekly tutorials led by a peer mentor which have been embedded into a one-semester Success Course to assist students transitioning to tertiary studies. The activities and material for the tutorials are interdisciplinary and can be adapted to a variety of central themes for a learning community or cohort-based program. Critical thinking and inquiry based learning exercises are integrated throughout the weekly meetings, and each session is designed to address a particular problem or bottleneck to learning. Peer mentors model individual responsibility and self-regulation and emphasise learning as a process rather than an end product. A series of small assignments with multiple opportunities for feedback, and high academic standards promotes increased confidence and skill levels.